On 𝐵𝐸-Semigroups - Sun Shin Ahn; Young Hee Kim (International Journal of Mathematics and Mathematical Sciences)
The notion of a 𝐵𝐸-semigroup is introduced, and related properties are investigated. The concept of left (resp., right) deductive systems of a 𝐵𝐸-semigroup is also introduced.